High-Quality Development of Digital Industrialization in China: Status, Problems, and Countermeasures - Jinshu Su; Siqing Shan; Liguo Shuai; Kun Tang; Xiufeng Sui; Yinong Li; Congxi Song; Xicheng Lu (中国工程科学)
The digital economy encompasses both the industrialization of digital technologies and the digital transformation of industries. Digital industrialization serves as the foundation of the digital economy and acts as a driving force for the digital transformation of industries. This study employs problem-oriented approaches, comprehensive gap analysis, and the combination of qualitative and quantitative methods to explore the tasks and approaches for the high-quality development of digital industrialization in China. The study systematically analyzes the policy guidance, technological advancement, and industrial practices of digital industrialization in major economies around the world. It examines the status, gaps, and weaknesses regarding digital industrialization in China, identifies the primary issues affecting the high-quality development of digital industrialization, and proposes key tasks and policy recommendations for promoting the high-quality development of China's digital economy. Specifically, efforts should focus on building a coordinated development system between the central and local governments, strengthening the research and development of common key technologies to promote the deep integration of technological and industrial innovations, and improving the innovation ecosystem of digital industrialization to promote the coordinated development of various innovation entities in digital industrialization. Furthermore, policy recommendations include constructing a technical framework for the value realization of digital factors, strengthening the construction of talent teams to build a highland for talent innovation in digital industrialization, and conducting deep international cooperation in digital industrialization to share the achievements of the digital age with countries along the Belt and Road.